Monitoring Penggunaan Formalin Pada Daging Ayam (Observation The Use Of Formalin In Chicken) - Roza Azizah Primatika; Heru Susetya; Arselia Kartika Sari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2015)
Chicken is one of source of animal protein which consumed by many people. Although the animal protein is needed as a source of nutrition, the product becomes a danger when contain of formalin. This study aims to determine the level of use of formaldehyde in chicken meat in Yogyakarta traditional markets and the factors associated with the incident. The samples used were 56 chickens, obtained from 11 traditional markets in Yogyakarta were chosen randomly. Each sample was tested using two reagent is phenylhydrazine and Quantofiq. Interpretation of test phenylhydrazine that is colored bluegreen solution and eventually turned into a red-orange color if the sample is positive, and yellow if it is negative. At Quantofiq test the color will be formed at the end of the detection paper, then color matched to the color table to determine levels of formaldehyde in the samples tested. The results showed that 6 (10,7%) positive samples contain of formaldehyde and analysis of Chi-Square showed that p_value = 0.045. So sales location were association with used of formaldehyde in chicken meat.